EHRA expert consensus statement on arrhythmic mitral valve prolapse and mitral annular disjunction complex in collaboration with the ESC Council on valvular heart disease and the European Association of Cardiovascular Imaging endorsed cby the Heart Rhythm Society, by the Asia Pacific Heart Rhythm Society, and by the Latin American Heart Rhythm Society - Sabbag, Avi; Essayagh, Benjamin; Barrera, Juan David Ramírez; Basso, Cristina; Berni, Ana; Cosyns, Bernard; Deharo, Jean-Claude; Deneke, Thomas; Di Biase, Luigi; Enriquez-Sarano, Maurice; Donal, Erwan; Imai, Katsuhiko; et al. (Europace, 2022)
[Figure: see text]
Keywords: Latinská Amerika; Latin America; nemoci srdečních chlopní; Risk stratification‌; Sudden cardiac death; Ventricular arrhythmia; Mitral annular disjunction; konsensus; Mitral Valve Prolapse; Consensus; Humans; Heart Valve Diseases; lidé; prolaps mitrální chlopně; Mitral valve prolapse; Mitral Valve; mitrální chlopeň